More on ideal limit points - He, Xi; Zhang, Hang; Zhang, Shuguo (Topology and its applications, 2022)
In this paper we continue the study of ideal limit points. We introduce a new combinatorial property of ideals called weakly P+, and investigate the relation between P+, weakly P+ and the complexity of ideal limit points. Moreover, we clarify the relation between ideal limit points, ideal cluster points and ordinary ideal limit points. Finally, we investigate the projective hierarchy of ideal limit points.